Action-related dynamic changes in inferior frontal cortex effective connectivity: A TMS/EEG coregistration study. (November 2018) - Zanon, Marco; Borgomaneri, Sara; Avenanti, Alessio
Abstract: Humans show exquisite abilities to perform versatile finger movements. The inferior frontal cortex (IFC) plays a pivotal role in the visual control of such movements through connections with other sensorimotor regions. Yet, the dynamics of IFC effective connectivity during action execution are still poorly understood. Using single-pulse TMS and simultaneous EEG recording (i.e., TMS-EEG coregistration), we stimulated the left posterior IFC at rest and during a visuomotor task. We recorded TMS-evoked potentials (TEPs) to assess action-related changes in IFC connectivity and localized their sources using sLORETA. We found two key time windows at ∼60 and ∼80 msec after IFC stimulation in which TEPs were modulated by task conditions in remote electrodes. In the first time window (∼60 msec), action-related changes in TEP amplitudes were observed over frontal and temporo-parietal electrodes, reflecting increased IFC connectivity with fronto-parietal motor areas and decreased IFC connectivity with visual occipito-temporal areas. In the second time window (∼80 msec), action-related TEP increases were observed in frontal, temporal and parietal regions partially overlapping with the default-mode network. No similar effects were observed when TMS was administered over a non-motor control area (the left posterior superior temporal sulcus, STS). These findings highlight dynamic changes in IFC connectivity with motor, sensory and default-mode networks. They suggest sequential stages of task-related changes in IFC connectivity possibly related to controlling and sensing actions and inhibiting default-mode brain activity during motor performance.